Emerging Trends in Neoadjuvant Immunotherapy for Hepatocellular Carcinoma: A Focus on Liver Transplant Candidates - Dongdong Yu; Hao Chen; Lidong Wang (Cancer Reports)
ABSTRACT Background Immunotherapy has emerged as a promising neoadjuvant strategy for hepatocellular carcinoma (HCC), with growing evidence supporting its role in tumor downstaging and enabling radical resection. Liver transplantation remains a curative option for HCC, and the integration of neoadjuvant immunotherapy prior to transplantation holds potential to improve staging outcomes and reduce postoperative recurrence. However, this approach necessitates careful evaluation of transplant‐related immunological risks, particularly the risk of allograft rejection. Recent Findings Recent clinical trials have provided key data on the efficacy and safety of pre‐transplant immunotherapy. These studies highlight the importance of patient selection and risk management strategies to optimize treatment outcomes. Novel immunotherapeutic approaches are being explored, with a focus on identifying patients most likely to benefit from neoadjuvant therapy prior to liver transplantation. Conclusion This review synthesizes emerging trends in the use of neoadjuvant immunotherapy for HCC patients undergoing liver transplantation. While immunotherapy shows promise in enhancing staging success and reducing recurrence, careful consideration of immunological risks and patient‐specific factors is essential. Future research should continue to evaluate the long‐term benefits and safety of this approach, as well as refine strategies for patient selection and risk mitigation. The integration of immunotherapy into pre‐transplant care may represent a transformative advancement in the treatment of HCC, provided these challenges are addressed.